Co(II) Based Magnetic Systems. Part I Spin Crossover Systems and Dendritic Frameworks. Part II Co(II) Single Molecule Magnets. - Farghal, Ahmed M. S. (Université d'Ottawa / University of Ottawa, 2012)
This work comprises two main parts. The first part outlines our efforts to expand on the recent work of Gütlich et.al. by synthesizing Co(II) based spin crossover systems within a dendritic framework. We wanted to investigate the possibility of synthesizing different first generation, triazole containing dendrimers using “click” type reactions and their coordination ability with Co(II) ions. To this end we have had limited success mainly due to the numerous challenges in synthesizing a pure dendrimer product. The second part details our efforts in the synthesis of a mononuclear Co(II) based single molecule magnet. This comes as an extension to recent reports by Chang and Long where they have successfully obtained mononuclear Fe(II) single molecule magnets by inducing structural distortions within the complexes to amplify the spin-orbit coupling. We postulated that the use of Co(II) in conjunction with a bulky ligand framework would lead to desirable magnetic properties. We chose the known bis(imino)pyridine ligand scaffold due to its rich chemistry and its interesting and unexpected coordination behaviour, as we have seen in previous research efforts by our lab. To this end we were successful in isolating and characterizing 4 compounds, and we have carried out detailed magnetic measurements on the two most magnetically interesting species.
Keywords: Cobalt; Co(II); Magnetism; single molecule magnet; spin crossover; magnetic anisotropy; dendrimers; click; bis(imino)pyridine; Farghal; Ahmed; spin orbit coupling; mononuclear; richeson; darrin; CCRI; University of Ottawa